1978
DOI: 10.2514/3.60895
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Hydrodynamic, Entropy, and Combustion Noise in a Gas Turbine Combustor

Abstract: This paper deals with noise sources which are centra! to the problem of core engine noise in turbopropulsion systems. The sources dealt with are entropy noise and direct combustion noise, as well as a nonpropagating psuedosound which is hydrodynaniic noise. It is shown analytically and experimentally that a transition can occur from a combustion noise-dominant situation to an entropy noise-dominant case if the contraction of a terminating nozzle to the combustor is high enough. In the conibustor tested, entrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 4 publications
0
33
0
Order By: Relevance
“…The problem was then termed entropy noise and correspondingly the density inhomogeneities or hot spots were called entropy waves [3,4]. It has been demonstrated that unsteady flames can generate entropy waves, which are advected downstream by the mean flow and may reach the exit nozzle of the combustor [3,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The problem was then termed entropy noise and correspondingly the density inhomogeneities or hot spots were called entropy waves [3,4]. It has been demonstrated that unsteady flames can generate entropy waves, which are advected downstream by the mean flow and may reach the exit nozzle of the combustor [3,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Two mechanisms control combustion noise generation, related to the propagation of these two waves to the outlet: direct noise, generated when acoustic waves traverse the turbine stages, and indirect noise, a mechanism in which entropy waves generate noise when accelerated with the mean flow. This source can contribute significantly to the total noise (Candel 1972;Pickett 1975;Muthukrishnan et al 1978). Recent studies (Bake et al 2009;Howe 2010;Leyko et al 2009Leyko et al , 2008 have shown that the propagation of waves through non-uniform flows plays a major role in the generation and attenuation of combustion noise.…”
Section: Introductionmentioning
confidence: 99%
“…Although the effects of noise or random excitations have been studied extensively in other elds (such as signal processing, economics and nance, and physics, to name a few 4 ), only a small amount of work has been done on the interactionsbetween noise and acoustic instabilities. Strahle,5,6 Muthukrishnan et al, 7 and Hedge and Strahle 8 studied combustion noise and possible interaction between noise and instabilitiesover a number of years.They concluded that the coupling between combustion noise and acoustic waves is not strong enough to drive large-amplitudeoscillations. 5¡ 8 Deur and Hessler 9 investigated external excitations as a possible explanation for large-amplitudeoscillationsin combustionchambers.As we will show, inclusion of noise will lead to external excitations that could theoretically produce large-amplitude forced oscillations as Deur and Hessler have suggested.However, there is a fundamental difference in the transient behavior of forced oscillationsand self-excited oscillations.…”
mentioning
confidence: 99%